Analisis Program Sekolah Ramah Anak dalam Upaya Pencegahan Perilaku Kekerasan - Nur Ayu; Supriadi Torro (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
In an effort to fulfill and protect children's rights, Child Friendly Schools are implemented. Child Friendly Schools are needed to create and transform traditional school models into child friendly schools that respect children's rights. This school model is effective in ensuring the protection of children's rights, preventing violence, discrimination and other unwanted actions and developing students' potential. The research was conducted at Polut 1 Public Middle School, Takalar Regency, South Sulawesi Province. The type of research used is qualitative research. The focus of this research is how the child-friendly school program is in an effort to prevent violent behavior. Types and sources of data used are primary data and secondary data. The research instruments used were observation and interviews. Data collection techniques and procedures, namely using observation techniques, interviews, and documentation. To create a child-friendly school, synergy and strong commitment are needed from all stakeholders in the school environment, an active role and positive attitude are required by all related parties, starting from school principals, teachers, students, parents must contribute their respective functions to create a climate a school environment that is safe, comfortable, and certainly does not contain elements of violence in it.